The performance of active investment positions in foreign markets - Fedenia, Mark; Skiba, Hilla; Sokolyk, Tatyana (Journal of International Business Studies, 2023)
We analyze whether cross-national distance between professional money managers and the positions they take in foreign markets affects investment performance. Out of four dimensions of cross-national distance (geography, culture, business climate, and industry), we find that only cultural distance inversely relates to portfolio performance. Investors earn higher returns in culturally similar foreign markets when market conditions in these countries are favorable. Our results show that the culture-based patterns in foreign portfolio allocations are associated with an information advantage and suggest that multinational corporate decisions influenced by culture increase firm value.